Collecting Duct Carcinoma of the Native Kidney in a Renal Transplant Recipient - Ian Zheng; Mahmoud Alameddine; Yaohong Tan; Zhobin Moghadamyeghaneh; Joshua S. Jue; Ali Yusufali; Ahmed Farag; Gaetano Ciancio (Case Reports in Transplantation)
Collecting duct carcinoma (CDC) is a rare and aggressive form of renal cell carcinoma (RCC) arising from the epithelium of Bellini’s duct. It presents earlier in life and has a poorer prognosis than the clear-cell type. Historically, immunosuppressed renal transplant patients are more likely to develop malignancies than the general population. We report a case of CDC of the native kidney in a 59-year-old man who initially underwent kidney transplantation five years before the time of presentation. To our knowledge, CDC in the setting of renal transplant and long-term immunosuppression has not been previously described.